Participação dos receptores semelhantes ao Toll na indução de expressão de mRNA para CXCL8 (IL-8) na infecção in vitro de células epiteliais por Campylobacter fetus subsp. Venerealis e Tritrichomonas foetus - Telma Maria Alves (2010)
The present study is about two of the most important sexually transmitted diseases in cattle, bovine genital campylobacteriosis and bovine genital trichomoniasis caused by Campylobacter fetus subsp. venerealis and by Tritrichomonas foetus respectively. In the first chapter, there is a literature review of the two diseases, focusing on aspects related to epidemiology, diagnosis, control measures, distribution, risk factors and immunity. In the second and third chapters, we studied the interaction of C. fetus subsp. venerealis and T. foetus with epithelial cells in vitro respectively. The kinetics of CXCL8 transcription in microorganisms were evaluated by RT-PCR using epithelial cells: HeLa, MDBK, HEK293, HEK293-TLR2, HEK293-TLR4/MD-2, after infection kinetics, with the use of specific primers for CXCL8, TLR2, TLR4, MD-2. In this study, the C. fetus subsp. venerealis NCTC 10354T strain, previously activated by three passages in virgin heifers, was able to induce the expression of CXCL8 via TLR2 in epithelial cells after 6 h indicating the involvement of this chemokine in the initial immune response against theorganism. T. foetus isolated from bovine female genital tract was able to induce the transcription of CXCL8 via TLR4/MD-2 18 h after infection. In both diseases the humoral response is well defined, however, is needed to compress the innate immune response, which will provide abetter understanding of the mucosal immunity in the genital tract, contributing to a greater knowledge of the pathogenesis.